2020
DOI: 10.1111/jam.14569
|View full text |Cite
|
Sign up to set email alerts
|

Production of fructooligosaccharides byBacillus subtilisnatto CCT7712 and their antiproliferative potential

Abstract: Aims: Fructooligosaccharides (FOSs) known for their health properties and b-(2?6)-levan-type FOSs have shown prebiotic and immunomodulatory activities that overcome those of commercial b-(2?1)-FOSs, but costs do not favour their use. Moreover, FOSs can reach the bloodstream through the diet, and little is known about their direct effect on cells. The aim of this work was to produce high-content FOSs by Bacillus subtilis natto CCT7712 in a bioreactor using commercial sucrose and to evaluate their antiproliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…β-(2,1)-fructans are extensively investigated for their effect on the immune response and have been shown to interact with TLRs to elicit their response. 21 Although β-(2,6)-fructans presented similar effects on the immune response in human in vitro studies, 22,24,25 the mechanisms underlying the immunomodulatory function of β-(2,6)-…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…β-(2,1)-fructans are extensively investigated for their effect on the immune response and have been shown to interact with TLRs to elicit their response. 21 Although β-(2,6)-fructans presented similar effects on the immune response in human in vitro studies, 22,24,25 the mechanisms underlying the immunomodulatory function of β-(2,6)-…”
Section: Discussionmentioning
confidence: 99%
“…β-(2,1)-fructans are extensively investigated for their effect on the immune response and have been shown to interact with TLRs to elicit their response. 21 Although β-(2,6)-fructans presented similar effects on the immune response in human in vitro studies, 22,24,25 the mechanisms underlying the immunomodulatory function of β-(2,6)-fructans are not well understood. Since it was shown that β-(2,1)-fructans elicit their immunomodulatory response through TLR interaction, 7,29 we hypothesized that similar mechanisms might be involved in the immunomodulatory effects of β-(2,6)-fructans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, this could be reduced by using enzymes and specific microorganisms. In this context, some parameters of the bioprocesses are determinants for FOS production [63], for example, temperature, pH, agitation speed, oxygen flow, and the culturing medium composition [56,63]. The worldwide increase in the demand for FOS requires new substrates and processes to reduce costs, as well as addressing the global problem of excessive generation of agro-industrial waste on the planet [17].…”
Section: Enzymes Involved In Fructooligosaccharides Productionmentioning
confidence: 99%